(Re)introducing critical realism as a paradigm to inform qualitative content analysis in causal educational research - Parra, Juan David; Said-Hung, Elías Manuel; Montoya-Vargas, Juny (International Journal of Qualitative Studies in Education, 2021)
This is article contributes to the debate on the empirical applications of critical realism (CR) in school effectiveness research. Researchers that endorse this research paradigm privilege intensive, over extensive, research designs, focussing, hence, in ethnographic methods and qualitative interviewing. However, and despite some recent academic proposals, there is little guidance in the literature on how to analyse qualitative data using the lenses of CR to produce causal knowledge about the operation of education policies in society. The current piece elaborates on the tenets of dialectical CR to develop some methodological arguments on how to engage in this type of empirical work. These reflections are then applied to analyse qualitative information retrieved in three 'failing' schools from Northern Colombia as an exemplar.
Keywords: School failure; qualitative analysis; dialectical critical realism; Colombia; Emerging; Scopus